Stock Price Reaction Analysis Before And After The Announcement Of The First Covid-19 PSBB Implementation On The LQ-45 Index Listed On The Indonesia Stock Exchange - FAJARIYAH, Saadila; DJASULI, Mohamad (Journal of Governance, Taxation and Auditing, 2022)
This study was conducted to determine the reaction of stock prices before and after implementing the PSBB for the first time. Stock price reactions were measured by abnormal returns and trading volume activity using the event study method with an adjusted market model approach. The population used in this arrangement is the number of companies listed on the LQ-45 index for the February-July 2020 period, as many as 45 companies. The sample used a saturated sampling technique for as many as 45 companies. This research data uses secondary data consisting of daily stock closing prices and daily stock trading volumes with an observation period of seven days before the event, one day when the PSBB was implemented, and seven days after the PSBB was implemented. The statistical tools used were the normality test and the one-sample t-test. The results of this study indicate that there is a significant average abnormal return. However, there is no difference in abnormal returns before and after implementing the first PSBB. Besides that, the results show a significant average trading volume activity. However, trading volume activity is the same before and after the first PSBB implementation.